ACQUISITION OF THE ARTICLE THEBY NONNATIVE SPEAKERS OF ENGLISH - Liu, Dilin; Gleason, Johanna L. (Studies in second language acquisition, 2002)
Linguistic analyses suggest that the nongeneric use of the English definite article the falls into four major categories: cultural, situation, structural, and textual. This study aims to determine whether these uses present different levels of difficulty for ESL students and whether they are acquired at the same time. The instrument consisted of 91 sentences containing 60 deleted obligatory uses of the (15 per category) and, as control items, 40 zero articles (10 per category) where the is not allowed. The participants (41 low-, 49 intermediate-, and 38 advanced-level students) were instructed to read the sentences and insert the wherever they deemed necessary. Statistical analyses of the participants' performance indicate the following: (a) The four nongeneric uses pose different levels of difficulty, which suggests that ESL acquisition of the is use dependent and follows a natural order; (b) The participants' performance on the suppliance of the in obligatory contexts for all four uses improved significantly with proficiency level, whereas the overuse of the followed a different pattern: an initial worsening followed by an improvement as the subjects' proficiency level increased. Pedagogical implications, including instructional sequence and strategies for the various uses of the, are discussed.